Jack [videorecording (DVD)] - Mestres, Ricardo; Fuchs, Fred; Coppola, Francis Ford, 1939-; Demonaco, James; Nadeau, Gary; Williams, Robin, 1951-2014; Lane, Diane; Lopez, Jennifer, 1970-; Kerwin, Brian; Drescher, Fran (Hollywood Pictures Home Entertainment, 2004)
Jack suffers from a disorder that makes him look 4 times as old as he is, so when the 10-year-old attends school for the first time, he runs into some obvious difficulties.